PROSTAGLANDIN ANALOG OR RHO KINASE INHIBITOR – WHICH ONE IS BETTER IN PRIMARY OPEN-ANGLE GLAUCOMA - OJHA, RICHA; CHAURASIYA, RAKESH CHANDRA; RANA, JAGRITI; KUMAR NIM, DWIVIDENDRA; SINGH, VIJAY KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The aim of the study was to compare the efficacy, safety, and adverse drug reactions of ripasudil and bimatoprost. Methods: An open-label, prospective, observational, randomized study was carried out in the Department of Pharmacology M.L.N. Medical College in association with Manohar Das Regional Institute of Ophthalmology, Prayagraj, for 1 year after ethical clearance. A total of 118 patients with primary open-angle glaucoma fulfilling the inclusion and exclusion criteria were taken and randomized into two groups. Only 109 patients completed the study, Group 1 received ripasudil (n=54) and Group 2 received bimatoprost (n=55). Intraocular pressure (IOP), ocular surface disease index (OSDI), tear brake-up time (TBUT), and hyperemia were measured at the initiation of treatment and then measured at different time intervals. Results: Group 1 and Group 2 patients were observed and followed up for 3 months. At the end of the 2nd, 4th, 6th, and 12th week in Group 1, ripasudil significantly showed better results in reducing IOP as compared to Group 2 bimatoprost. In terms of TBUT, both groups at the 12th week did not show any significant difference. The OSDI score of both groups showed a non-significant difference at the 12th week. At the end of 2nd week, hyperemia was comparable for both groups but ripasudil showed more hyperemia at the end of the 12th week. Conclusion: We concluded that ripasudil is more effective than bimatoprost in reducing IOP in patients with primary open-angle glaucoma. In terms of adverse effect profile, both drugs showed similar effects in TUBT and OSDI scores. The safety profile of both drugs is similar but the hyperemia score of ripasudil is more than bimatoprost.